By the numbers and in their own words: A mixed methods study of unmet needs and humanitarian inclusion of older Syrian refugees in Lebanon. - Sarah Al Omari; Gladys Honein-AbouHaidar; Abla Mehio Sibai (PLoS ONE, 2024)
Older people constitute an overlooked vulnerable population in humanitarian crises. Lebanon is a small country that hosts the largest number of refugees per capita in the world. With exacerbating socioeconomic conditions, exclusionary policies against refugees, and a fragmented humanitarian system, the status of older Syrian refugees (OSRs) requires special attention. This study aimed to explore OSRs' unmet needs, coping strategies, available humanitarian services, and some indicators of the humanitarian inclusion standards focusing on the shelter, health, nutrition and food security, and water, sanitation and hygiene sectors. We conducted a convergent mixed-methods study between December 2021 and March 2022 in the North and Bekaa, including a cross-sectional survey with 461 participants and 14 semi-structured interviews. Results show that OSRs lived in inappropriate shelters (cold, leaking rainwater), especially in informal tented settlements. High rent prices pushed refugee households with elderly to prioritize paying rent at the expense of other needs such as food and medication, particularly when food cash transfer is the sole source of income, jeopardizing food security and intake. Access to dignifying and accessible bathing facilities was compromised in ITSs with shared facilities. Substantial medical costs hindered OSRs access to healthcare such as surgeries. Due to the crisis, chronic medications are not always available in dispensaries for subsidized cost, pushing OSRs to non-compliance and selling food assistance to buy medications. Soaring fuel prices hindered OSRs access to heating and transportation to receive healthcare. No efforts were reported in collecting data on OSRs' needs, targeting them with information on services, or soliciting feedback for programming, especially in the absence of any age-tailored interventions. Findings shed light on the precarious living conditions of OSRs in Lebanon and add to the body of evidence documenting their invisibility to the humanitarian response. An age-inclusive response is needed through holistic, tailored, and sustainable interventions.